Mapping Potential for Improving Rural Energy Services in Kyrgyzstan: Factors for Achieving Sustainable Development Goals in the Community Context - Kedar Mehta; Mathias Ehrenwirth; Christoph Trinkl; Wilfried Zörner (World, 2022)
Energy is a pivotal element for overall development. Therefore, affordable and clean energy for all (Sustainable Development Goal 7) is one of the important elements. Despite a suitable approach, Kyrgyzstan lags behind to achieve its Sustainable Development Goals by 2030. Improving access to energy can significantly impact the progress of many other sustainable development targets. However, access to reliable, sustainable, and adequate energy is a crucial task in rural Kyrgyzstan. Taking into consideration the energy situation and the importance of the availability of energy services, the overarching aim of the presented article is to map the potential of improving rural energy services to foster overall sustainable development goals. The article presents the most relevant information about rural energy usage behaviour based on three primary pillars: energy demand, energy carrier, and energy sources. In addition, the presented research article synthesises the key driving factors which have a direct or indirect impact on the energy services in rural areas. The summarised data displays a deep insight into a variety of complex and dynamic household energy consumption patterns. The article provides a potential solution nexus to foster improved energy services in rural Kyrgyzstan and therefore to foster the overall sustainable development in Kyrgyzstan. The findings of the article help to formulate a strategy to design rural energy services for policy makers and stockholders.